ANALISIS RELASI PERSAHABATAN DITINJAU DARI INTERAKSI SOSIAL DAN ORIENTASI INDIVIDU - Varlina, Vivi; Dewi Safira, Angelia; Raiha Yasmin, Mutia (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Human life cannot be separated from the relationship with its environment. The need for relationships requires the creation of understanding in each particular behavior. However, it turns out that it is not easy to create understanding between individuals. The increasingly complex needs of human life are one of the obstacles to establishing interpersonal communication, making it difficult to achieve good relationships. Therefore, it requires individuals to review the person they are talking to or orient themselves after carrying out social interactions. This research focuses on the influence of social interaction and individual orientation in terms of inclusion, control and affection using the Fundamental Theory of Interpersonal Relations Orientation (FIRO). Based on research and exploring the relationship between variables, researchers involved 51 respondents who qualified as generation Z with ages 18-25 years and came from various regions in Indonesia. The analysis states that there is a correlation between the influence of social interaction and individual orientation on the friendship relationships that Generation Z currently has.